PERLINDUNGAN HUKUM TERHADAP DOKTER DI RUMAH SAKIT UMUM DAERAH SELE BE SOLU KOTA SORONG TAHUN 2011 - , INDRIYANI LINDAWATY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to obtain information about legal protections and responsibilities of the hospital against doctors who perform duties at the Hospital General Regional Sele Be Solu Sorong as the implementation of Hospital Act No.44 of 2009 Article 29 paragraph (1) points S and article 46. This research is juridical normative and empirical research using primary and secondary data consisting of primary law materials, and secondary law materials and analysis using qualitative analysis, namely data analysis by describing the legislation in force. The data obtained in this study was chosed based on the issues studied, analyzed and linked and linked to theories that relate to legal and health problems posed in this study. The study is the Law Hospital Act No.44 of 2009 Article 29 paragraph (1) point S and Article 46 which regulates the legal responsibilities of the hospital in terms of providing protection and legal assistance for physicians who work in hospitals have not implemented well in the Regional General Hospital Sele Be Solu Sorong, this is because not all medical staff (medical specialists, general practitioners and dentists) as well as management of the hospital staff know about the Law Hospital No.44 in 2009 so there has been no implementation of the Act which resulted All the doctors who worked at the General Hospital Regional Sele Be Solu slide City have not received a guarantee of Legal Protection in the hospital in carrying out his profession to become a doctor